Moderando la influencia de la diversidad idiosincrásica en las relaciones entre la ética contable y la calidad de los informes financieros; Moderating influence of idiosyncratic diversity on the relationship between accounting ethics and financial reporting quality - Ofuan.James Ilaboya; Oscar Chijioke Mgbame; Okhae James Ibhadode; Godwin Ohiokha (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
– Purpose- The study investigates the moderating influence of idiosyncratic diversity on the relationship between accounting ethics and financial reporting quality, against the backdrop of the unending corporate collapses and their antecedent effect on the profession of accounting.Design/Methodology/Approach- The study is anchored on the positivist philosophy with a deductive research strategy. We employed theoretical triangulation having combined agency theory and resource dependency theory. The sample size of three hundred and eighty-four respondents was established using the Cochran (1977) approach for the infinite population. Primary data were collected for the study through a survey approach and analysed using the Ordinary Least Squares regression technique.Findings- The study validates the significant relationship between accounting ethics and financial reporting quality in extant literature. In addition, we found a significant moderating influence of idiosyncratic diversity on the relationship between accounting ethics and financial reporting quality.Practical implications- The study demonstrates the strategic importance of accountants of diverse nationalities in delivering quality financial reporting in Nigeria.Research limitations/implication- The research is a country-wide study of accountants in Nigeria which enhances the extensive generalization of the outcomes.Originality/value- While extant studies have mainly been preoccupied with the accounting ethics-financial reporting dynamics, the current study focuses on understanding the moderating influence of idiosyncratic diversity on the relationship between accounting ethics and financial reporting quality. In addition, the country-wide approach adopted circumvented the limitation of micro numerosity of data which has been the bane of major prior studies.
Keywords: M14; M49; 330; Idiosyncratic diversity; financial reporting quality; accounting ethics; integrity; Professional behaviour